DETERMINATION OF SOME PESTICIDE RESIDUES IN VEGETABLES (OKRO, SORREL AND SPINACH) SAMPLES FROM FORI, JERE LOCAL GOVERNMENT AREA, BORNO STATE, NIGERIA - Auwalu, Aliyu S.; Baba, Abdullateef; Abdullahi, Mohammed I. (FUDMA JOURNAL OF SCIENCES, 2024)
This study is aimed at determining the levels of some pesticide residues in vegetable samples (Sorrel, African spinach and Okro) from the Fori area of Jere. The vegetable samples were collected at three different sampling points designated F1 to F3. Extraction and clean-up of vegetable samples were carried out using standard procedures. The levels of the pesticide residues in the vegetable samples were determined using GC-MS. Dichlorvos was observed (178 – 2814.5 mg/kg) in all the samples from the three locations. In location, F3, 16 mg/kg and 11 mg/kg of cypermethrin were observed in okro and spinach respectively. In location, F2, 3979 mg/kg and 3220 mg/kg of cyhalothrin was observed in Okro and spinach respectively. Diazinone (3380 mg/kg) was observed only in F2 (sorrel).  The concentrations of the detected pesticides in all the three vegetable samples from the three locations were greatly higher than the Minimum Regulatory Limit (MRL) values. When comparing our result with that agricultural standard (TAS 9002-2013) we found out that our MRL value is far higher than the institute value. As such we recommended that the farmers in Fori should be properly trained and directed on how to use pesticides and another related chemical to avoid health risks and toxic effects on the farmers, the plants and generally to the consumers.